BRAVE: Terminal year end report - Malaya, Justin Ryan C. (Animo Repository, 2022)
In the Philippines, there is an evident increase in the number of cases and incidents that involve robbery, assault, crime, and rape. With it becoming more rampant, the safety and well-being of Philippine citizens have gradually decreased most especially to the Filipino workers and students that commute and utilize public transportation in the country. The Global Peace Index (2018) ranks the Philippines 23rd out of 163 countries as having the least safety, security domain, and peace. The harsh reality among all this is that victims of such situations have no means of self-defense and, in turn, injuries and even fatalities eventually occur. Other times, people that do carry self-defense weapons such as pepper sprays are unable to equip themselves quick enough since it is usually stored in their bags, delaying the time it takes to pull these out and put them to proper use. This is concrete evidence to prove how safety is a need for individuals residing in the Philippines and the founders seek to utilize this situation as an opportunity to cater to the needs of Filipino citizens. Due to these circumstances, the founders of BRAVE Inc. incorporated themselves to develop a self-defense product that provides functionality and convenience in the form of a wearable pepper spray bracelet. Conceptualized by BRAVE Inc, Bravelet is a silicone bracelet that is worn on the wrist with an attached spray bottle mechanism for pepper spraying. That way, their mode of self-defense is more accessible and users are able to protect themselves without experiencing any difficulty as opposed to those who do not have any form of self-defense or those who keep them in their bags. Bravelet is light and compact, all ready to use. It comes in the color black to appear discreet and to match the user's outfits. The homemade pepper spray mixture contains natural ingredients that are sourced from the local market making it cost-effective. In lieu of the changing times of COVID-19, the company also included an alcohol bottle in every order of Bravelet since sanitation and cleanliness are needed with the ongoing pandemic. The group utilized this situation as a way to increase sales since alcohol is needed in all places we go. The alcohol spray bottle is a swappable option during this pandemic crisis but also gives the user the opportunity to still use Bravelet within the workplace. During the 8 months of operations, the company has primarily sold products through the online platforms, Instagram, Facebook, and Shopee. However, personal selling amongst the owners contributed a significant amount of sales to the business. With a board meeting occurring every month, the company has meticulously planned the advertising content being published weekly. This systematic approach allowed BRAVE Inc. to have a timeline and calendar that shows the details of every content and when it will be posted. BRAVE Inc. has recognized the importance of promoting and advertising, thus, numerous methods have been implemented in promoting the product. From conducting photoshoots, creating commercials, and also memes, BRAVE Inc. is committed to ensuring that the products are being effectively promoted. With over 372 units sold in 10 months, the company stands as an operating business that has consistently promoted bravery amongst Filipinos in the country. The group has earned a total net income of Php 25,304.21 and a return of investment of 42%. Through the consistent effort being given by the members, the company was able to plan and strategize the best ways of generating income and reaching customers.